Analisis Faktor Penentu Kepuasan Masyarakat Penerima Pelayanan Publik Studi kasus di kelurahan Lubuk Buaya Padang - Asrizal Windi Aprio Ramadhan (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2015)
This study is based on the phenomenon, there still exists the public to get services that require a long time, and there are still unscrupulous employees who are not friendly in the service, so the question arises, what is the level of community satisfaction of services and what are the factors that influence satisfaction. The purpose of research to determine the level of satisfaction and the factors that influence it. The analysis technique used in this research is to regress independent variable to the dependent variable. The results showed determinants of satisfaction in a sequence that is tangible, responsive, assurance, reliability, and empathyKey Word: kepuasan masyarakat, pelayanan publik